Women's Leadership in Humanitarian Institutions Asar Humanity Foundation - Puti Halimah (INJECT (Interdisciplinary Journal of Communication), 2024)
Women have leadership potential in humanitarian institutions. However, women are considered unsuitable to become leaders because they are soft and emotional. This research aims to provide an overview of women's leadership (Nyai) in leading Islamic boarding schools. The method used in this research is qualitative case study research. This research gathered information from four selected informants: the CEO, institutional managerial level leaders, and Asar Humanitarian Foundation staff. From the research results, it was found that the leadership of the humanitarian organization Asar Humanity Foundation (Nyai) considered the charismatic, transformational, transactional, and visionary leadership styles to be suitable to implement. However, the leadership style that was most suitable for the CEO of this organization was transformational leadership. Transformational leadership is considered to inspire the team under the CEO, which aligns with institutional values ​​that all members of the organization should internalize.